Inflation in mainland China: modelling a roller coaster ride - Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
The New Keynesian Phillips curve (NKPC) posits the dynamics of inflation as forward looking and related to marginal costs.In this paper we examine the empirical relevance of the NKPC for mainland China.The empirical results indicate that an augmented (hybrid) NKPC gives results that are consistent with the data generating process.It is in this respect that the NKPC provides useful insights into the nature of inflation dynamics in mainland China as well as useful insights for the conduct of monetary policy.
URN:NBN:fi:bof-201408072079
Keywords: C22; E31; 330; China; inflation; New Keynesian Phillips curve